1.9 Ga eclogite from the Archean-Paleoproterozoic Belomorian Province, Russia - Li, Xiaoli; Yu, Huanglu; Zhang, Lifei; Wei, Chunjing; Bader, Thomas (Science Bulletin, 2017)
The first Archean eclogite was announced from the Salma and Gridino complexes of Belomorian Province (Russia) in Fennoscandian Shield (Fig. 1a) [1] that has aroused quite a resonance worldwide from all aspects; the debates on the actual age of the Belomorian eclogites have never stopped ever since and in all there are three scenarios are suggested (1) one time in Mesoarchean, (2) two times in Neoarchean and Paleoproterozoic and (3) one time in Paleoproterozoic [2]. Actually, most early geochronological investigations were conducted only on the intensely retrogressed eclogite samples, including the alleged Mesoarchean 2.87-2.82 Ga Fe-Ti eclogite from Uzkaya Salma complex [3,4], but no actual eclogite of omphacite-bearing assemblage was ever analyzed here. In this work, we firstly discovered a fresh bi-mineralic eclogite (sample UzS-3) associated with intensely retrogressed analogue (sample UzS-4) from the Uzkaya Salma (sub-)complex of Belomorian Province (Fig. 1b) that may significantly revise the previous points of view regarding the Archean eclogitic metamorphism and related geodynamic regime of Belomorian Province in whole. National Nature Science Foundation of China [41202032, 412111062, 41311120071] SCI(E) 中国科学引文数据库(CSCD) EDITORIAL MATERIAL 4 239-241 62